Cardiac left ventricular mass and arterial stiffness from childhood to early adulthood - association with cardiometabolic risk factors : the Special Turku Coronary Risk Factor Intervention Project (STRIP) - Mikola, Hanna (fi=Turun yliopisto|en=University of Turku|, 2018)
Background: Cardiac left ventricular mass and arterial stiffness are subclinical markers of cardiovascular disease which are associated with cardiovascular disease and clinical events in adulthood. Aims: The aim of this thesis was to study left ventricular mass and arterial stiffness in childhood and their determinants in terms of cardiometabolic risk factors and ideal cardiovascular health. This thesis also aimed to investigate the effect of a dietary and lifestyle intervention on ideal cardiovascular health and subclinical markers of cardiovascular disease. Subjects and methods: This thesis is a part of the prospective, randomized Special Turku Coronary Risk Factor Intervention Project (STRIP) that has followed initially over 1,000 children for 27 years. Their cardiometabolic risk factors have been repeatedly measured from childhood to adulthood. Children in the intervention group (n=540) have received dietary and lifestyle counseling aimed at improving the quality of dietary fat. Subclinical markers of atherosclerotic cardiovascular disease were examined using noninvasive ultrasonic measurements of carotid and aortic distensibility, pulse wave velocity, carotid intima-media thickness and cardiac left ventricular mass. This study analyses the data of the children who participated in the arterial ultrasound evaluations from the age of 11 to 19 years (n=420–503), and in the cardiac ultrasound assessments from the age of 15 to 19 years (n= 394–420). Results: Cardiac left ventricular mass and arterial stiffness increased with increasing age from childhood to early adulthood. In boys, the arterial stiffness increased more than in girls. It was found that current pulse pressure, weight and physical activity along with birth weight were associated with left ventricular mass in adolescence; overall these factors explained nearly 50% of the variation in left ventricular mass. Childhood blood pressure, body mass index, LDL cholesterol concentration and insulin resistance were associated with arterial stiffness. The dietary and lifestyle intervention was associated with ideal cardiovascular health in adolescence, however, it had no effect on left ventricular mass or arterial stiffness. Conclusions: Marked age-related arterial stiffening is evident already in childhood, particularly in boys. Several cardiometabolic risk factors determine arterial stiffness and cardiac structure already at an early age. Although the dietary and lifestyle intervention promoted ideal cardiovascular health in adolescence, the intervention did not change the subclinical markers of cardiovascular disease at this early age.

Sydämen vasemman kammion massa ja valtimoiden jäykistyminen lapsuudesta varhaiseen aikuisuuteen – yhteys kardiometabolisiin riskitekijöihin. Sepelvaltimotaudin Riskitekijöiden Interventioprojekti (STRIP) Tausta: Sydämen vasemman kammion massa ja valtimoiden jäykistyminen ovat valtimoterveyden varhaismarkkereita, jotka ovat yhteydessä sydän- ja verisuonisairauksien päätetapahtumiin aikuisiällä. Tavoite: Väitöskirjatutkimuksen tavoitteena oli tutkia vasemman kammion massaa ja valtimoiden jäykistymistä lapsuudessa, sekä selvittää niitä määrittäviä tekijöitä kardiometabolisten riskitekijöiden ja ihanteellisen sydänterveyden mittareiden avulla. Lisäksi tutkimuksen tavoitteena oli selvittää ravitsemus- ja elämäntapaneuvonnan yhteyttä ihanteelliseen sydänterveyteen ja valtimoterveyden varhaisiin muutoksiin. Menetelmät: Väitöskirjatutkimus on osa prospektiivista, satunnaistettua Sepelvaltimotaudin Riskitekijöiden Interventioprojekti (STRIP) -tutkimusta, jossa on seurattu 27 vuoden ajan alun perin yli 1000 lasta. Tutkittavien lasten sydän- ja verisuonisairauksien riskitekijät on mitattu toistuvasti lapsuudesta aikuisuuteen. Ateroskleroottisen sydän- ja verisuonitaudin varhaisia muutoksia tutkittiin mittaamalla ultraäänellä kaulavaltimon ja aortan distensibiliteetti, pulssiaallon etenemisnopeus, kaulavaltimon intima-median paksuus sekä sydämen vasemman kammion massa. Interventioryhmän lapset (n=540) ovat saaneet ravitsemus- ja elämäntapaneuvontaa, jonka päätavoitteena on ollut ruokavalion rasvan laatuun vaikuttaminen. Tässä työssä käytettiin niiden lasten tietoja, jotka osallistuivat valtimoiden ultraäänitutkimukseen 11– 19 vuoden iässä (n=420–503) ja sydämen ultraäänitutkimukseen 15–19 vuoden iässä (n=394–420). Tulokset: Sydämen vasemman kammion massa kasvoi ja valtimot jäykistyivät lapsuudesta varhaiseen aikuisuuteen. Pojilla valtimoiden jäykistyminen oli voimakkaampaa kuin tytöillä. Tutkimuksessa havaittiin, että pulssipaine, paino ja liikunta sekä syntymäpaino olivat yhteydessä vasemman kammion massaan nuoruudessa selittäen lähes 50 % variaatiosta. Lapsuudessa mitattu verenpaine, painoindeksi sekä seerumin LDL-kolesterolipitoisuus ja insuliiniresistenssi olivat yhteydessä valtimoiden jäykistymiseen lapsuudesta varhaiseen aikuisuuteen. Ravitsemus- ja elämäntapaneuvonta oli yhteydessä ihanteelliseen sydänterveyteen nuoruudessa, mutta sillä ei havaittu olevan yhteyttä valtimoiden jäykistymiseen tai vasemman kammion massaan Johtopäätökset: Valtimot jäykistyvät iän myötä jo lapsuudessa - erityisesti pojilla. Useat kardiometaboliset riskitekijät ovat yhteydessä valtimoiden jäykistymiseen ja sydämen rakenteeseen jo varhaisella iällä. Ravitsemus- ja elämäntapaneuvonnalla voidaan edistää ihanteellista sydänterveyttä nuoruudessa, vaikkakaan se ei ollut yhteydessä valtimotaudin varhaismarkkereihin näin varhaisella iällä.